2008
DOI: 10.1002/jcu.20479
|View full text |Cite
|
Sign up to set email alerts
|

High‐flow priapism complicating ischemic priapism following iatrogenic laceration of the dorsal artery during a Winter procedure

Abstract: ABSTRACT:We report a case of a patient who developed high-flow priapism following a Winter procedure performed for the treatment of low-flow ischemic priapism. During the creation of bilateral cavernosal-glandular shunts, the tip of the left dorsal artery was accidentally lacerated. A fistula developed through the shunt between the torn artery and the cavernosal sinusoids of the tip of the left corpus cavernosum. Gray-scale and Doppler sonography and angiography allowed diagnosis and guided the therapeutic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…Several authors have noted that following either aggressive medical management of ischemic priapism with aspiration and intracavernous alpha‐adrenergic injections or surgical shunting that priapism may rapidly recur with conversion from ischemia to high flow. High‐flow priapism has been reported following medical and surgical management of ischemic priapism [47–49]. Color Doppler ultrasound in these cases reveals formation of an arteriolar‐sinusoidal fistula as in typical high‐flow priapism or, on rare occasion, a high‐flow hemodynamic state of the cavernous arteries with no evident fistula formation.…”
Section: Epidemiology and Pathophysiology Of Priapismmentioning
confidence: 98%
“…Several authors have noted that following either aggressive medical management of ischemic priapism with aspiration and intracavernous alpha‐adrenergic injections or surgical shunting that priapism may rapidly recur with conversion from ischemia to high flow. High‐flow priapism has been reported following medical and surgical management of ischemic priapism [47–49]. Color Doppler ultrasound in these cases reveals formation of an arteriolar‐sinusoidal fistula as in typical high‐flow priapism or, on rare occasion, a high‐flow hemodynamic state of the cavernous arteries with no evident fistula formation.…”
Section: Epidemiology and Pathophysiology Of Priapismmentioning
confidence: 98%
“…Few idiopathic cases have been described [12]. There are a few reports of iatrogenic causes after treatment for a low-flow state [1316] and there is one due to an iatrogenic laceration of the cavernosal artery [17]. This series describes two cases of high-flow priapism after surgical intervention to treat a low-flow state.…”
Section: Introductionmentioning
confidence: 99%
“…They may later represent to other physicians with erectile dysfunction after getting married or when sexually active. Bertolotto et al 18 reported a case of high flow priapism following Winter shunt due to injury to dorsal artery. This rare complication was observed in one patient in our series which was managed conservatively.…”
Section: Discussionmentioning
confidence: 99%